Analysis of the Utilization of the Online Learning Media Platform at Madrasah Aliyah Featured KH. Abdul Wahab Hasbullah - M Wafiyul Ahdi; M Khoirul Anwar Gholibi (SCHOOLAR: Social and Literature Study in Education, 2022)
The purpose of this study was to analyze the effectiveness of online learning at KH. Abdul Wahab Hasbullah's Excellent Madrasah Aliyah. The research method used is descriptive qualitative. The data collection technique was carried out by the researcher using the interview method with several subjects as a research source, namely the curriculum waka and several subject teachers in KH. Abdul Wahab Hasbullah's Superior Aliyah Madrasah. Respondents said madrasah E-Learning, Google form, Google meet, and WhatsApp were the most preferred access for teachers, because they were easy to use and were free of charge. Google Drive and Zoom are rarely used because Zoom has to use a strong network which causes the classroom atmosphere to be less conducive due to differences in the strength of the student network. Finally, the researchers' suggestions for increasing the effectiveness of online learning for educators, namely: Teachers should open themselves to learning and make positive learning innovations, especially in implementing online learning strategies using interesting and fun methods, and listening to input from students.